The 5' flanking region of the gene for the Epstein-Barr virus-encoded nuclear antigen 2 contains a cell type specific cis-acting regulatory element that activates transcription in transfected B-cells. - Ricksten, A (1988)
We have recently identified the promoter that positions the initiation (cap) site for RNA encoding the Epstein-Barr virus (EBV) determined nuclear antigen 2 (EBNA2) in transfected COS-1 cells. The cells were transfected with recombinant vectors that contained the BamHI WYH region of the EBV genome. In order to delineate regulatory DNA sequences required for the expression of EBNA2 the 5' flanking region of the gene was linked to reporter genes in expression vectors and transfected into EBV genome-negative lymphoid DG75 cells. We demonstrate that several cis-acting elements contribute to a transcriptional enhancer activity found in the region between nucleotides-553 and -86 relative to the cap site. The enhancer was active in lymphoid DG75 cells but not in HeLa cells and stimulated transcription also from the heterologous thymidine kinase (TK) and beta-globin promoters. Nuclear extracts of lymphoid cells contained protein factors that bound to the enhancer. The in vitro introduction of a mutation in the enhancer sequence that substantially reduced the transcription stimulatory activity concurrently blocked the binding of one of the factors.